2020
DOI: 10.1051/e3sconf/202022404009
|View full text |Cite
|
Sign up to set email alerts
|

State of microbiocenosis of southern chernozem under the no-till system

Abstract: Agricultural technologies aimed at reducing the tillage can be adopted as safer farming methods to preserve and improve the diversity of soil microbial communities. The area under the promising resource-saving no-till system (direct sowing) is increase in the conditions of the Steppe annually. The use of herbicides in such a farming system causes a negative effect on the soil biocenosis. But the introduction of agronomically useful microorganisms into the rhizosphere are increasing the resistance of plants aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…As a source of microbiota, we chose chernozem, a soil type common in the southern regions of Russia. Cellulolytic capabilities of the chernozem microbiome were reported earlier [ 24 , 25 ]. Our team has already worked with chernozem and demonstrated that it can be a potential source of cellulolytic microorganisms by both traditional microbiology and molecular methods [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 63%
“…As a source of microbiota, we chose chernozem, a soil type common in the southern regions of Russia. Cellulolytic capabilities of the chernozem microbiome were reported earlier [ 24 , 25 ]. Our team has already worked with chernozem and demonstrated that it can be a potential source of cellulolytic microorganisms by both traditional microbiology and molecular methods [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 63%
“…Straw introduction into the soil creates a surplus of nutrients, specifically carbon compounds, which facilitates a new path in the microbiota succession [24]. Earlier we demonstrated that chernozem is a potential source of cellulolytic microorganisms by both traditional microbiology and molecular methods [25,26]. Here we attempted to analyze the process of colonization of the lignocellulosic substrate by the chernozem microbiota and identify its most prominent phases.…”
Section: Discussionmentioning
confidence: 99%